(untitled) (Journal of Ideas in Health, 2026)
Background: As in other organisms, the normal performance of rodents depends on health status of all the body systems including the oral cavity and associated structures. Any deviation from normal function of the oral cavity or teeth results in a complex clinical sign that may be related to other systems secondarily. The current case report describes four dental conditions encountered in the Silvery mole rat (Heliophobius argenteocenerius emini) kept at Sokoine University of Agriculture, Tanzania. Case presentation: Three out of twenty-two animals developed dental conditions associated with mandibular and maxillary incisors. Based on clinical presentations, the conditions were closely assessed under general anaesthesia using xylazine-ketamine protocol at 5 and 50 mg/kg respectively. Detailed examination revealed that all the three animals had more than one dental condition including incisor overgrowth, lateral deviation, malocclusion of different levels ranging from mild to severe and fractured incisor tooth presented as pseudo-oligodontia. Severe incisor overgrowth and malocclusion were managed by coronal reduction of the clinical crown. Conclusion: The current report highlights few dental conditions encountered in the Silvery mole rats. Malocclusion of the incisors was common to all the three animals signifying that this probably is the most common dental condition in this species as reported in other rodents. Detailed studies are recommended to explore more on the prevalence of dental and periodontal diseases of this rodent group. Keywords: Silvery Mole Rat, Incisor Overgrowth, Lateral Deviation, Malocclusion and Incisor Fracture, Tanzania